2007
DOI: 10.1021/ct600329w
|View full text |Cite
|
Sign up to set email alerts
|

AMBER Force Field Parameters for the Naturally Occurring Modified Nucleosides in RNA

Abstract: Classical molecular dynamics (MD) simulations are useful for characterizing the structure and dynamics of biological macromolecules, ultimately, resulting in elucidation of biological function. The AMBER force field is widely used and has well-defined bond length, bond angle, partial charge, and van der Waals parameters for all the common amino acids and nucleotides, but it lacks parameters for many of the modifications found in nucleic acids and proteins. Presently there are 107 known naturally occurring modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
295
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(302 citation statements)
references
References 48 publications
3
295
2
Order By: Relevance
“…27 Aduri et al constructed a model of the E. coli 30S ribosome with all of the modifications present. 46 The results show that the methyl groups in m 2 G966 and m 5 C967 extend their stacking surface areas. The extended surface contact stabilizes the rather unusual 970 loop structure, which has few intra-loop H-bond interactions.…”
Section: Importance Of the 966 967 And 968 Stackmentioning
confidence: 91%
See 1 more Smart Citation
“…27 Aduri et al constructed a model of the E. coli 30S ribosome with all of the modifications present. 46 The results show that the methyl groups in m 2 G966 and m 5 C967 extend their stacking surface areas. The extended surface contact stabilizes the rather unusual 970 loop structure, which has few intra-loop H-bond interactions.…”
Section: Importance Of the 966 967 And 968 Stackmentioning
confidence: 91%
“…In addition, the methyl group of m 2 G966 is within van der Waals contact of Arg128 of protein S9 in the T. thermophilus 30S structure with m 2 G966 modeled in, suggesting that m 2 G966 stabilizes S9 binding through hydrophobic interactions. 19,24,46 The base of 966 interacts with the backbone of the P-site tRNA at position 34 20 and in the saturation mutagenesis showed a preference for purines. We found that among the functional mutants, adenosine was present more often than m 2 G at position 966.…”
Section: Importance Of the 966 967 And 968 Stackmentioning
confidence: 99%
“…Molecular Dynamics Simulations-Atomistic explicit solvent simulations of minimally structured U 5 (GC)U 5 , U 4 ⌿(GC)U 5 , U 5 (GC)⌿U 4 , and U 4 ⌿(GC)⌿U 4 RNA constructs were performed using the GROMACS (Groningen Machine for Chemical Simulations (29 -32) molecular dynamics package on the local ACISS (Applied Computational Instrument for Scientific Synthesis) cluster at the University of Oregon, using an AMBER (Assisted Model Building with Energy Refinement) (33) force field optimized for stem-loop RNA structures with modified force-field parameters for the ⌿ base (34). All simulations were performed in explicit solvent utilizing the spc/e water model and 150 mM NaCl with excess sodium ions to neutralize the system, Ewald summation for the electrostatics, and standard force-field cutoffs and parameters.…”
Section: Methodsmentioning
confidence: 99%
“…All pairs were solvated and neutralized using the AMBER 9 xleap module to render the pairs. Modifications were added by replacing individual molecule designations in unmodified base Protein Data Bank (PDB) files with those from the RNA modified parameters database (Aduri et al 2007) and were matched by comparison using Chimera (Pettersen et al 2004) to produce new functional PDB files. Bases were initially minimized in vacuum to reach optimum geometries from which periodic restraint angles were determined.…”
Section: Methodsmentioning
confidence: 99%